Application of the shear wave elastography in the assessment of carotid body tumors: A preliminary study - Zhang, Xiaoyan; Zheng, Yuehong; Li, Jianchu; Zhang, Bo (Frontiers in Oncology, 2023)
Objectives: To evaluate the elasticity of carotid body tumors (CBTs) by two-dimensional shear wave elastography (SWE). Methods: 22 pathologically or clinically confirmed CBTs in 16 patients were scanned by SWE. The maximum elasticity value (Emax) and its standard deviation (SDmax) in kPa and m/s for CBTs were obtained by placing a round ROI (2-3 mm) on the stiffest region of the CBTs. Elasticity value was compared between hard and soft groups at manual palpation, benign and malignant groups and among three Shamblin types. The area under the receiver operating characteristic curve (AUC) analysis was performed to evaluate the performance of SWE in the malignancy prediction of CBTs. Sensitivity, specificity and accuracy were calculated. The cut-off value was obtained by using the Youden index. Results: There were 19 benign CBTs and 3 malignant CBTs. Emax (kPa and m/s) and SDmax (kPa) were significantly higher in the hard group than in the soft group at manual palpation (P＜0.05); The distribution of Emax in kPa and m/s and SDmax in kPa were different in the three Shamblin types (P＜0.05), Emax (kPa and m/s)increased from shambling I to Shambling II and Shambling III; Emax (kPa and m/s) were significantly higher in the malignant CBTs than in the benign ones (P＜0.05). Emax in kPa and m/s had the similar AUC value (AUC=0.947, P=1.0000) for the prediction of malignant CBTs. Emax in kPa with the cut-off 124.9kPa showed a sensitivity of 100.0%, specificity of 94.7%, and an accuracy of 95.5% (Z=8.500, P＜0.0001); Emax in m/s with the cut-off 5.9m/s showed a sensitivity of 100.0%, specificity of 89.5% and an accuracy of 90.9% for the prediction of malignant CBTs (Z=9.143, P＜0.0001).